Mempelajari Komponen Sistem Informasi Manajemen - Rizky Alpiansyah; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
The use of information systems is very much needed in this era of technological progress which is increasingly increasing rapidly as well as in organizations where it is used in making decisions. To make logical decisions, information systems are very important. This means that one must understand the problem and know the alternative solutions. Better decisions are made with more precise information. Accurate (accurate), timely (timely), and relevant are three factors that determine the quality of information. The factors that must be considered in decision making are as follows: the purpose of the decision; identification of decision alternatives to solve problems; calculations about events that cannot be known in advance or are beyond human control (uncontrollable events) and means or tools used to evaluate or measure the results of decision making.